Comments on nonlinear dynamics asymmetric behavior in bi-stable energy harvesters - Ribeiro, Mauricio A.; Daum, Hilson H.; Tusset, Angelo M.; Balthazar, Jose M. [UNESP]; Silva, Rodrigo N.; Machado, Raphaela C. [UNESP]; Litak, Grzegorz (Springer Nature, 2023)
In this work, we explore the nonlinear dynamics for capturing energy from a device, which is considered support with cantilever beam ferromagnetic containing piezoceramic patches connected to an electrical circuit that collects energy for capture. The free end of the ferromagnetic cantilever beam is under the effect of two magnetic poles, and we consider an asymmetric potential for the magnetic poles. However, the influence of asymmetry in bi-stable energy collectors can change the potential well and adjust the distribution of its potential energy. Charging in the potential well also modifies the unstable equilibrium positions thus altering the dynamic characteristics of the device and thus benefiting the use of energy under various excitation conditions. Furthermore, asymmetric potentials combine with the movement of human lower limbs for applications in energy harvesting devices in such displacement. As numerical results, we explored the nonlinear dynamics and established the sets of parameters for the convergence of the trajectories and the regions of maximum average output power.
Keywords: Energy harvesting; Nonlinear dynamics; Potential asymmetric